Membangun Generasi Berkarakter : Kekuatan Pendidikan Dalam Keluarga - Anisa Anisa; Muhammad Iqbal; Dina Mardiana; Redha Anshari (JURNAL ILMIAH NUSANTARA, 2025)
Character education is the main foundation in forming a generation that is not only intellectually smart, but also morally and spiritually strong. This article aims to examine in depth the role of the family in the process of children's character education in the midst of globalization and the challenges of digitalization. This research uses a library research approach with descriptive qualitative analysis of various sources such as scientific journals, books, and previous research results. The results of the study show that families, especially parents, have a strategic role as the first educators who instill values such as honesty, responsibility, discipline, empathy, and religiosity through modeling, habituation, and effective communication. In addition, families also play an important role in shaping national resilience through the cultivation of national values and local culture. Supervision of digital media, the application of appropriate parenting, and harmonization in the household environment are important factors in the success of character education. Thus, character education in the family is a long-term investment to produce a superior generation that is ready to face the challenges of the times.